Kondisi Kebisingan di Gedung Perkuliahan Universitas Bengkulu - Abdul Rahman Singkam (University of Bengkulu, 2020)
Learning activities require a conducive condition, including liberated of noise. This research aims to analyze the noisy level during learning activities in some lecture building of Universitas Bengkulu (UNIB). The data was collected through systematic purposive sampling and analyzed descriptively. The level of sound at UNIB lecture buildings (GKB) 1 until 5, I and J buildings was measured every five minutes during the interval 08.01 - 08.30, 08.31- 09.00, 10.01 - 10.30, 11.16 - 11.45 and 13.01 - 13.30 (local time) for a day sampling. The results show the sound intensity at UNIB lecture buildings ranges from 46.6 to 89.8 dBA, with most of the data (81%) were categorized as noisy, and above the threshold for education environment. The noise level was significantly different between buildings (X2=78.50, df=5, P<0.001) and between time interval (X2=79.09, df=29, P<0.001). The lowest average of noise was in J building i.e. 58.85 dBA + 1.30, while the highest was in GKB 5, 68.15 dBA + 0.87. Based on the time interval, the lowest average was at 13.01-13.30 i.e. 59.20 dBA + 1.45, while the highest at 10.01-10.30, 71.58 dbA + 1.86. This noise level was parallelly correlated with the estimation number of students using the building (F1,4=43.87, p < 0.001, R2=0.92), which indicated the main source for these noises are student activities. A high level of noise at UNIB lecture buildings need to be treated. A long term of noise can affect physiology and psychology of the students and reduce the effectivity of learning.